Avenues for increasing salt tolerance of Tunisian durum wheat cultivars - Chaabane R.; Saidi A.; Rouissi M.; Ben Naceur E.; Mejri C.; Ben Naceur M. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Salt-tolerant durum wheat cultivars offer great potential to grow them in marginal lands. To develop high-yielding, salt-tolerant cultivars for the various salt-affected areas of Tunisia we adopt two approaches. The first approach is the study of genetic variability for salt tolerance within Tunisian varieties using agro-physiological traits. We studied numerous agro-physiological traits but only few of them change very significantly and contribute to the salt tolerance mechanism. This allowed us to choose reliable screening traits and criteria useful for germplasm breeding programmes. The second approach is the introgression of Nax genes into elite Tunisian varieties by marker-assisted backcrossing (MAB). These Nax genes reduce leaf [Na+] and increase durum wheat grain yield on saline soils.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)